Usaha Budidaya Jamur Tiram Putih (Pleurotus ostreatus) Untuk Mendukung Jiwa Kewirausahaan di Sekolah Menengah Kejuruan - Suharno Suharno; Supeni Sufaati; Rosye H.R. Tanjung; Mahmudi Mahmudi; Irma Rahayu; Yuliana Yuliana; Wetty Queenisa Kabes (Jurnal Surya Masyarakat, 2024)
White oyster mushroom (Pleurotus ostreatus) is one type of mushroom as a source of vegetable food that is widely favored by the public. The quality of mushrooms that contain high protein, healthy food sources, and suitable for all groups. In Indonesia, the cultivation business has started to develop and not only among entrepreneurs, but also the general public. Efforts to understand cultivation need to be carried out from an early age, including in schools, so that it can become the basis for developing students' interests, especially related to entrepreneurship program activities. The purpose of this activity is to provide understanding, practice, and business of white oyster mushrooms at SMK YPKP Sentani. The methods used were FGDs, cultivation practices and small-scale cultivation businesses at the school level. The results of the activity showed that the students were enthusiastic in participating in the activity. After the activity all participants have recognized and understood the shape and morphological structure of mushrooms. This activity increased the understanding of white oyster mushroom cultivation by 175.3%, from 34.05% to 93.74%, and understanding of marketing potential reached 183.8% from 29.9% to 85.7%. Moreover, the results of their cultivation through mentoring can be successfully carried out independently at the school level. Businesses that are carried out with simple technology, and produce quality products are very attractive to them in entrepreneurship.